High-resolution insights into the early stages of silver nucleation and growth - Völkle, C.; Gebauer, Denis; Cölfen, H. (R S C Publications, 2015)
© The Royal Society of Chemistry 2015.Nucleation and growth of silver nanoparticles has already been investigated with various experimental and computational tools. However, owing to inherent problems associated with the analytical characterization of nucleation processes, there is a general lack of experimental data regarding the earliest precursors and smallest Ag(0) clusters. Here, we address this problem by the application of Synthetic Boundary Crystallization Ultracentrifugation, utilizing a multiwavelength detector for the first time, complemented by a specialized titration assay. These techniques shed new light on silver nanoparticle precursors existing in the pre-nucleation regime, and the initially nucleated ensemble of nanoclusters. For the first time, we present experimental data of UV-Vis spectra for fractionated silver clusters. These allow for unsurpassed insights into the sequence of nucleation and early growth species as well as their optical properties.